Comparison analysis of PD-1/PD-L1 inhibitors plus lenvatinib or gemcitabine/cisplatin as first-line treatment for patients with advanced intrahepatic cholangiocarcinoma - Huang, Jia-Xin; Liu, Bo; Li, Yu; Li, Xi; Ding, Li-Juan; Wang, Nan-Ya (Frontiers in Oncology, 2023)
Background Intrahepatic cholangiocarcinoma (ICC) is a highly aggressive primary liver cancer, with increasing incidence worldwide. Effective first-line treatments for advanced ICC patients are currently limited. Therefore, our study aimed to assess the efficacy and safety of programmed death-1 (PD-1)/programmed death-ligand 1 (PD-L1) inhibitors in combination with gemcitabine/cisplatin (GC) and lenvatinib as first-line treatment in advanced ICC patients. Methods This retrospective cohort study included 51 advanced ICC patients, among whom 25 patients were administered with PD-1/PD-L1 plus lenvatinib and 26 patients were administered with PD-1/PD-L1 plus GC. Baseline characteristics including demographic information, medical history, clinical characteristics, laboratory data, and imaging examination were collected. The primary endpoints were progression-free survival (PFS) and sixth- and ninth-month overall survival (OS) rate. Survival curve was plotted by the Kaplan–Meier method. A Cox proportion risk model was performed to investigate independent risk factors of PFS and OS. The secondary outcomes were objective response rate (ORR), disease control rate (DCR), and adverse events. Results The median age of advanced ICC patients in our study was 58.0 (95% confidence interval [95% CI] = 48.0–72.4) years, with 33 male and 18 female patients. Patients in the PD-1/PD-L1 inhibitors plus lenvatinib group were more likely to be in ECOG grade above 1, develop ascites, and have an elevated level of ALT. The ORR was 16.0% in the PD-1/PD-L1 inhibitors plus lenvatinib group and 23.1% in the GC group (p = 0.777). The DCR was 52.0% in the lenvatinib group and 46.2% in the GC group (p = 0.676). The combination treatment of PD-1/PD-L1 inhibitors plus lenvatinib was associated with longer PFS than the GC group; however, it was not statistically significant (lenvatinib: 9.5 months, GC: 5.1 months, p = 0.454). The sixth-month and ninth-month OS rates were 82.0% and 76.9% in the lenvatinib group and 87.4% and 71.5% in the GC group. After adjusting for confounders, multivariate Cox regression analysis showed that ECOG grade above 1 was an independent risk factor for PFS (hazard ratio [HR] = 3.388, 95% CI = 1.312–8.746, p = 0.012) and OS (HR = 4.220, 95% CI = 1.131–15.742, p = 0.032). Conclusion PD-1/PD-L1 inhibitors in combination with lenvatinib or GC all demonstrated significant efficacy and safety as first-line treatment in patients with advanced ICC. As for patients who refuse or are intolerant to chemotherapy, PD-1/PD-L1 plus lenvatinib would be recommended.